KONSTRUKSI LANGEN TAYUB NGANJUK DALAM PERSPEKTIF BERGERIAN - Anik Juwariyah (Jurnal Budaya Nusantara, 2014)
Internalization’s phase of society as a subjective fact implies that the objective reality interpreted subjectively by the individual. In a process of interpreting that internalization took place. Internalization is the process experienced by humans to ‘take over’ the world that are inhabited neighbor. Internalization lasts a lifetime involving socialization, both primary and secondary. Developing knowledge in agrarian societies instituted in continuous tradition and heredity.In theory of Berger and Luckmann, this sort of thing is to be part of a social construction, in particular objectivationstage. For Berger, is a product of human society, rooted in externaliation phenomenon. Langen tayub is seen as a knowledge that is maintained and applied through tradition and process interactions that exist in society.Keywords: Langen Tayub construction, Nganjuk, Bergerian.